Pre-SEMMS: A Design of Prepaid Smart Energy Meter Monitoring System for Household Uses Based on Internet of Things - Kurniawan D. Irianto (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
The use of prepaid smart electricity services from the State Electricity Company (SEC) for the general public in Indonesia has increased. It is because prepaid electricity has several advantages compared to postpaid electricity. One of them is that it is becoming easier for customers to manage and control their daily electricity usage. Customers can also estimate their total electricity consumption each month. However, customers still have to manually view the information on the electricity meter to find data and information on prepaid electricity. It can make it difficult for customers if the electricity meter is placed outside the house, which is quite far away. Customers must also constantly monitor the use of electricity. This article discusses a prepaid smart electricity consumption monitoring design using Internet of Things technology. The design is carried out without changing the standard prepaid electricity meter system from the SEC. However, a KWH meter tool has been developed that has been combined with Internet of Things technology and can calculate and monitor electricity usage. The results show that with this system, customers can more easily find out and monitor their daily electricity consumption.